A readable Beowulf : the Old English epic newly translated - Greenfield, Stanley B. (Southern Illinois University Press, 1982)
The Anglo-Saxon poem recounting the story of Beowulf's battle with the monster, Grendel, is translated in the style of contemporary verse.